Persepsi Manfaat Penggunaan Siantar.Dukcapil.Online oleh Masyarakat Kota Pematangsiantar - Saragih, Nurhafifah; Aisyah, Siti (Lembaga Yasin AlSys, 2022)
This study aims to see how the people of the city of Pematangsiantar view the emergence of using the website siantar.dukcapil.online which was just implemented during the pandemic and the benefits felt after using the website issued by the Pematangsiantar city population and civil registration office. The methodes used in this research are interviews, literature studies and questionnaires for website users. The results obtained are the influence of the benefits received using the UTAUT (The unified Theory of Acceptance and Use of Technology) method variables which are interconnected.